Comprehensive analysis of particulate matter, gaseous pollutants, and microbiological contamination in a clothing store from an international chain in Europe - Furst, Leonardo (2025)
In this study, indoor air quality was assessed in a store belonging to one of Portugal's largest commercial retail groups. A variety of methodologies were used, including gravimetric analysis for particulate matter (PM), optical monitors for real-time PM measurements, gas sensors and analyzers for CO2 and other gaseous pollutants, diffusion tubes for VOCs, and passive deposition for microorganisms. The average PM10 concentration indoors was 16.5 ± 3.87 μg/m3, well below the exposure limits set by various international organizations. A significant portion of indoor PM10 – 69% - was originated from outdoor sources. Outdoor PM10 concentrations were substantially higher, averaging 29.4 ± 14.6 μg/m3. Metal concentrations were also higher outdoors than indoors, and the associated cancer risk and hazard quotient were not exceeded, indicating favorable air quality conditions within the store. Among VOCs, α-pinene and tetrachloroethylene were detected in notable concentrations. α-Pinene likely originated from cleaning products and fragrances, while tetrachloroethylene was attributed to emissions from a dry-cleaning establishment located in the same building, but did not exceed protection thresholds. Microbial analysis showed low concentrations of both fungi and bacteria. However, fungal species with clinical and toxigenic potential were found. The most common fungal species were Trichoderma sp. and Penicillium sp., depending on the culture media. Overall, the clothing store demonstrated good air quality. However, to further reduce the impact of outdoor pollutants on indoor air quality, enhancements to the ventilation system are recommended. These improvements can help create a healthier indoor environment by filtering and managing the intake of external contaminants more effectively.